Transcriptome Analysis Revealed the Mechanisms Involved in Ultrasonic Seed Treatment-Induced Aluminum Tolerance in Peanut - Bao, Gegen; Zhou, Qi; Li, Shengyu; Ashraf, Umair; Huang, Suihua; Miao, Aimin; Cheng, Zhishang; Wan, Xiaorong; Zheng, Yixiong (Frontiers in Plant Science, 2022)
Ultrasonic (US) treatment is an efficient method to induce crop tolerance against heavy metal toxicity, however US-induced aluminum (Al) tolerance in peanut was rarely studied. The present study was comprised of two treatments i.e., CK: without ultrasonic treatment, and US: ultrasonic seed treatment for 15 min. Both treated and non-treated treatments were applied with Al in the form of AlCl3.18H2O at 5mmol l-1 in Hoagland solution at one leaf stage. Results depicted that plant height, main root length, and the number of lateral roots increased significantly under US treatment. Transcriptome analysis revealed that plant hormone signal transduction and transcription factors (TFs) were significantly enriched in the differentially expressed genes (DEGs) in US treatment, and the plant hormones were measured, including salicylic acid (SA) and abscisic acid (ABA) contents were substantially increased whilst indole acetic acid (IAA) and jasmonic acid (JA) contents were decreased significantly in US treatment. The TFs was verified by qRT-PCR, and it was found that multiple TFs genes were significantly up-regulated in US treatment, and ALMT9 and FRDL1 genes were also significantly up-regulated in US treatment. Overall, the US treatment induced the regulation of hormone content, and regulated gene expression by regulating TFs to improve Al tolerance in peanut. This study provided a theoretical rational for US treatment to improve Al-tolerance in peanut.